CHARTER’S LIABILITY ON DEMURRAGE: AN INDONESIA’S PERSPECTIVE - Puti Diamar, Raisha; Chandrawulan, An an (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
ABSTRACTCarriage of goods plays a substantial role for both domestic and international trade in pursuance of fulfilling the markets’ supply and demand. Amongst all modes of carriage of goods, carriage of goods by sea is deemed to be the most effective mode — cost and quantity wise. However, carriage of goods by sea has a high possibility towards time indiscipline which could result to huge amount of damages, one of which concerning demurrage caused by expiration of laytime. In its practice, problems tend to arise when parties exert to determine the liability of demurrage. Hence, this article aims to discuss further regarding the concerned liability of demurrage. This article used descriptive analytical method, discussing limitation of liability terms written on bill of ladings and laytime exception clauses. Keywords: Bill of Lading, Carriage of Goods by Sea, Laytime & Demurrage